Organização e gestão pedagógica das escolas do Programa Ensino Integral (PEI) - Silva, Ana Beatriz Santos (Universidade Federal de São Carlos, 2025)
Integral education has historically been related to the increase of students' time in school but also marked by discussions and challenges regarding the realization of training that is, in fact, integral in all its dimensions. There has been a great expansion of public schools of integral education in the last decade, driven by national legislations and policies. In São Paulo State, the Integral Education Program (PEI) has grown significantly, and this study seeks to understand how schools have organized and managed the expansion of hours in the training of students, identifying program guidelines for training activities planning and the pedagogical challenges faced by professionals, based on qualitative bibliographical research. The results indicate that PEI schools face structural and pedagogical limitations that burden professionals and reduce their autonomy. The extension of school time has not necessarily guaranteed better training, because bureaucratic activities have also increased, impairing pedagogical work. For a truly integral education, profound changes are needed that value school autonomy and commitment to full education.
Organization and pedagogical administration of the schools of the Integral Education Program (PEI)
Keywords: Programa Ensino Integral; PEI; Educação integral; Organização escolar; Gestão pedagógica; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL::ADMINISTRACAO DE UNIDADES EDUCATIVAS; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL::ADMINISTRACAO DE SISTEMAS EDUCACIONAIS